Emerson's framework on the output of public-private partnership on hemodialysis services in Indonesia regional hospitals - Masyitoh Basabih; Eko Prasojo; Amy Yayuk Sri Rahayu (Global Transitions)
Context: Public-private partnerships (PPPs) have become the dominant solution adopted by regional hospitals in Indonesia for providing hemodialysis equipment. Analyzing the implementation of PPPs requires using a collaborative governance framework to provide a comprehensive analysis and depict the relationships between variables. This study aims to determine the influence of system context, drivers, and collaborative processes on the outcomes of PPP hemodialysis services in regional hospital in Indonesia. Methods: This study employs a quantitative approach with primary data obtained through a survey. The research sample consists of 75 regional hospitals represented by 111 respondents. Analysis was conducted using the Partial Least Square-Structural Equation Modeling (PLS-SEM) technique. Findings: The system context indirectly influences the process through mediation by the driver variable at 0.451, where the driver significantly affects the collaborative process at 0.534, and the collaborative process significantly influences the outcome at 0.773. The policy dimension makes the largest contribution to the systemic context, as does the consequential incentive dimension to the drivers. In the process variable, the capacity for joint action is the dimension with the greatest contribution. Conclusions: The outcomes of implementing PPP in hemodialysis services at regional hospital are influenced by system context, drivers, and collaborative processes both directly and indirectly. Policy barriers, human resources, and corrupt practices also affect the process and outcomes of hemodialysis PPP, which are perceived not to be in line with good governance.